Teachers’ Problems in Teaching Reading Skill: A Case Study at SMPN 8 Dulupi - Dian Oktaviani Ahmad; Rahmawaty Mamu; Helena Badu (Research Review: Jurnal Ilmiah Multidisiplin, 2022)
There were some problems faced by teacher during the process of teaching reading skill. These problems were hard to be figured out by the teacher in SMP Negeri 8 Dulupi. Thus this research was conducted to find the empirical data which observed in detail related to these problems. Moreover, the dominant explanation of this research took an aim to find out the teachers’ problems in teaching reading there were deciding the appropriate method, students’ less motivation and interest, students’ lack of vocabulary, limited facilities in teaching, overcrowded class and not enough material sources. This research took the method of qualitative research through observation and interview as the technique of collecting the data and took teacher of SMPN 8 Dulupi as the participant of research. The researcher had examined the aim of this research and it was found that the biggest problems faced by the teacher were deciding the appropriate method, students’ less motivation and interest, students’ lack of vocabulary, limited facilities in teaching, and not enough material sources while the overcrowded class was not affecting the teaching reading process since the amount of students in the class was well-handled.